2015
DOI: 10.1016/j.tox.2015.07.014
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal chlorpyrifos exposure induces loss of dopaminergic neurons in young adult rats

Abstract: Increasing epidemiological and toxicological evidence suggests that pesticides and other environmental exposures may be associated with the development of Parkinson's disease (PD). Chlorpyrifos (CPF) is a widely used organophosphorous pesticide with developmental neurotoxicity. Its neurotoxicity, notably on the monoamine system, suggests that exposure of CPF may induce dopaminergic neuronal injury. We investigated whether neonatal exposure to CPF contributes to initiation and progression of dopaminergic neurot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 68 publications
0
26
0
1
Order By: Relevance
“…Additionally, Ahmed et al [76] have previously reported similar changes of brain neurotransmitters after OPs exposure. Additionally, exposures to pesticides have been reported to cause permanent alterations in GABAergic, serotonergic [77], and dopaminergic systems [78]. …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Ahmed et al [76] have previously reported similar changes of brain neurotransmitters after OPs exposure. Additionally, exposures to pesticides have been reported to cause permanent alterations in GABAergic, serotonergic [77], and dopaminergic systems [78]. …”
Section: Discussionmentioning
confidence: 99%
“…However, chronic professional and even household exposure may lead to increased PD risk [ 87 , 88 ]. In animals, neonatal exposure to the chlorpyrifos led to long-term dopaminergic cell loss and microglial activation [ 89 ]. A case-control study found that higher rates of ambient organophosphate exposure were associated with higher PD risk [ 33 ].…”
Section: Pesticidesmentioning
confidence: 99%
“…The morphology of cells also greatly improved after pre-supplemented with gnetol as compared with malathion treatment alone ( Figure 1B). Previously, researchers found that subcutaneous exposure of young adult rats to chlorpyrifos promotes substantial nigral dopaminergic neuronal deathmediated development of neurodegeneration, and also led to intense accumulation of microglia-and astrocyte-related neuroinflammation [19]. Similar to gnetol, pentoxifylline protects rat brains from malathioninduced oxidative stress by enhancing antioxidative enzyme levels and antioxidants, and also by functioning as an immunomodulator [20].…”
Section: Discussionmentioning
confidence: 99%